Modelling of Gauss's Law Application for Electromagnetic Fields and Waves Courses - Ahmad Po’ad, Farhana; Lawasa, Nurul Hasmiera Afiqa (Evolution in Electrical and Electronic Engineering, 2021)
Nowadays, there are several alternatives that are used by students and lecturers for teaching and learning purposes. With the rapid technology enhancement, it is easier to improve the study method for a better understanding and problem-solving. Electromagnetic Field and Waves Theory (EMT) is an important course in engineering fields this can be used as an example to improve the teaching and learning method. This course is to introduce the fundamental of electromagnetic including electrostatic, magnetostatic, and electromagnetic waves. The main laws governing the electrostatic and magnetostatic are discussed thoroughly in this course as well. Among the important law is Gauss’s Law, which states that the net electric flux through any closed surface is equal to the net electric charge within that closed surface.  To solve any problem using  Gauss‟s  Law, students need to have a  better understanding of how to imagine the situation and have a strong background in multivariate calculus, especially on integration and differentiation. Therefore, an application utilizing  Gauss‟s  Law is developed to help students in imagining the movement of the electric charge,  as well as providing the solution using  Gauss‟s Law without performing manual mathematical solution as a reference before or during problem-solving in the EMT courses. The development of this project is an alternative to help students and lecturers to learn and teach this course in a better way.  The application focuses on  Gauss‟s  Law only and it is developed using MATLAB R2017a software. Users able to customize the value needed and the application will do the calculation according to the requirement from users and the outcome will be given in terms of C/ m2 (electric charge density, D). The outputs obtained from the application shows good agreement with manual calculation. The application can be further upgraded to include other laws related to Electromagnetic fields and Waves in the future.